Binge Eating Leading to Acute Gastric Dilatation, Ischemic Necrosis and Rupture –A Case Report - Dewangan, Manish (J Clin Diagn Res, 2016)
Acute gastric dilatation is a rarely encountered clinical scenario in our day to day practice. This is very rapidly progressing condition and can lead to ischemic necrosis and perforation/rupture of the stomach. It could be fatal if not timely intervened. We report such a case of a 17-year-old, otherwise healthy boy, who presented with pain and distension of abdomen following binge eating episode after 24 hours of prolonged fasting. On exploration, stomach was dilated with necrosis and perforation at fundus near greater curvature. He was managed with excision of all the devitalized area and primary repair with feeding jejunostomy. The case is presented due to its rarity. Acute gastric dilatation (AGD) leading to ischemic necrosis and perforation because of binge eating episode in an otherwise healthy person is an exceptional occurrence with only few cases reported in literature. The clinician should be aware of this condition for prompt and appropriate management.